MEMBANGUN MODEL BUDAYA PENEGAKAN HUKUM YANG BERBASIS ANTI KORUPSI: (Studi Kasus Polrestabes X) - Hadi Purnomo; Siti Rosimah; Ciavi Adinda Giantri Katim; Nina Kurniasari (Jurnal Hukum Lex Generalis, 2023)
Law enforcement should ideally uphold the values of human rights, transparency, non-discrimination, anti-corruption. In fact, the opposite, so created a corrupt legal culture in the law enforcement process. The research aims to explore the various dominant factors created by a corrupt culture in the law enforcement process. The results of the study, namely the conditions of the existing legal culture of the police environment in the law enforcement process, showed a tendency opposite to the one that should be in the legal process. The driving factors include hedonism, low incomes, permissive police leadership, lack of sovereignty, pressure from various sides. The ideal legal culture model is to change the sanctioning of violations of the law enforcement process through disciplinary sanctions.